Design and implementation of an FPGA-based NoC for Real Time Systems - Ribot, Yilian (2020)
In order to communicate, cores of a multi-core platform traditionally relied on shared busses. However, with the increasing number of computation nodes integrated in multi- and many-core platforms, Network-on-Chips (NoCs) emerged as a new alternative communication medium in Systems-on-Chips (SoCs). Hoplite-RT is a new NoC design that was recently proposed. Hoplite-RT is a compact design easy to analyze and with a low-cost implementation that was specifically tailored for FPGA. In this work, we introduce priority-based routing to Hoplite-RT and change the network topology so as to improve its timing behavior, i.e., its Worst-Case Traversal Time (WCTT).